The burden of air quality in neighborhoods near oil fields: an alarm for public health in Basra city, Iraq - Kadhum, Safaa A.; Hussain, Lujain Ibrahim; Azeez, Omer Saud; Abed, Salwan Ali; Jaafar, Ban Ibrahim (Springer Nature, 2025)
One of the important issues facing oil-exporting countries is poor air quality, which causes many health problems among the local population. The study evaluated the influence of meteorological conditions on air pollution in oil fields, which impacts the environment and public health in Basra city. The study also investigated the temporal and spatial changes in air pollution in the study area. The results indicated that meteorological conditions and air quality altered from 2019 to 2022, particularly for temperature, CH4 and NO2, which exhibited an increase in 2022 relative to 2019. Multivariate analysis, such as the correlation coefficient, showed wind speed a negative link with CO, O3, and CH4, as well as a as a weak positive link between temperature and NO2. A principal component study (PCA) was employed to identify the primary contributors to air pollution in Basra city. The study revealed that the main sources of air pollution were the emissions from oil fields and nearby oil refinery companies. In addition, the PCA analysis indicated that meteorological variables, specifically wind speed, were found to have an impact on the levels of CO, O3, and CH4. Hence, this study is valuable for making informed decisions to alleviate the detrimental environmental impacts on human beings. Additionally, this data holds potential value for future research endeavours aimed at managing and mitigating pollutants stemming from oil refineries.